2019
DOI: 10.1186/s12935-019-0862-6
|View full text |Cite
|
Sign up to set email alerts
|

The ionophore antibiotic gramicidin A inhibits pancreatic cancer stem cells associated with CD47 down-regulation

Abstract: Background Pancreatic cancer stem cells (CSCs), a special population of cells, renew themselves infinitely and resist to various treatment. Gramicidin A (GrA), an ionophore antibiotic derived from microorganism, can form channels across the cell membrane and disrupt cellular ionic homeostasis, leading to cell dysfunction and death. As reported, the ionophore antibiotic salinomycin (Sal) has been proved to kill CSCs effectively. Whether GrA owns the potential as a therapeutic drug for CSCs still re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
(44 reference statements)
0
15
0
5
Order By: Relevance
“…C-Myc also increases CD47 expression in pancreatic cancer. 119 C-Myc increases the transcription of CD47 in cancer cells. CD47 is located on the surface of cancer cells and interacts with signal-regulatory protein alpha (SIRP-α) to induce tolerance in immune cells, prevent cancer cells phagocytosis, and prolong cancer cells survival in pancreatic cancer.…”
Section: The Effect Of C-myc On Cancer Cells Metabolismmentioning
confidence: 98%
“…C-Myc also increases CD47 expression in pancreatic cancer. 119 C-Myc increases the transcription of CD47 in cancer cells. CD47 is located on the surface of cancer cells and interacts with signal-regulatory protein alpha (SIRP-α) to induce tolerance in immune cells, prevent cancer cells phagocytosis, and prolong cancer cells survival in pancreatic cancer.…”
Section: The Effect Of C-myc On Cancer Cells Metabolismmentioning
confidence: 98%
“…GA is known to form ion channels, which can allow monovalent ion (Na + and K + ) diffusion, resulting in changes in intracellular osmolality, and finally in cell death [25]. Recently, its antitumoral effect on renal cell carcinoma [26,27], gastric cancer cells [28], or pancreatic cells [29] was reported. Moreover, it was shown that GA used in combination with curcumin kills the cells expressing the multidrug-resistance-linked ABCG2 transporter by stimulated depletion of ATP levels [30].…”
Section: Introductionmentioning
confidence: 99%
“…Chloride influx Mitochondria-dependent apoptosis [40] Potassium Helical polypeptide Potassium efflux ER stress-mediated apoptosis [23] Valinomycin Potassium efflux Restoration of T cell immunity [31] Salinomycin Potassium efflux Suppression of Wnt pathway [6] Gramicidin A Potassium efflux Downregulation of CD47 [49] Calcium Helical polypeptide Calcium overload Mitochondria-dependent apoptosis [24] Calcium NPs Calcium overload Mitochondria-dependent apoptosis [59,[62][63][64] Tumor calcification [59,64] Zinc Clioquinol Zinc overload Inhibiton of NF-𝜅B pathways [ 68,115] Disulfiram Zinc overload Lysosomal disruption [69] Zinaamidole A Zinc overload Non-apoptotic cell death [11] Zinc NPs Zinc overload Oxidative stress-mediated apoptosis [ 71,73,74,77] PAC-1 Zinc depletion Autophagic cell death [ 75,116] Ferroptosis via disruption of iron homeostasis [76] VEGF inhibition [79] Manganese Manganese NPs Manganese overload Chemodynamic activity via Fenton-like reaction [84][85][86][87][88]117] MnO x nanospikes-nanovaccine Manganese overload Ferroptosis via Fenton-like reaction [89,90] Activation of cGAS/STING pathway [91] Ferroptosis-mediated ICD [90] Iron Tannic acid-based NP Iron overload Ferroptosis via Fenton reaction [21] Salinomycin analogue Iron overload Ferroptosis in cancer stem cells [9] Oxidized Starch Iron overload Ferroptosis via Fenton reaction [97] Iron NPs Iron overload Ferroptosis via Fenton reac...…”
Section: Chloride Ionophoresmentioning
confidence: 99%
“…[6] According to several reports, potassium ionophores are likely to activate antitumor immunity by pumping out intracellular potassium ions. [49] Gramicidin A has been used to reinforce antitumor immunity by suppressing an immune checkpoint. [49] The CD47 receptor is known as immune checkpoint that helps cancer cells prevent phagocytosis by antigen-presenting cells (APCs).…”
Section: Potassium Ionophoresmentioning
confidence: 99%